Argument against the Routine Use of Steroids for Pediatric Acute Respiratory Distress Syndrome - Hartmann, Silvia M.; Hough, Catherine L. (Frontiers in Pediatrics, 2016)
Steroids have a plausible mechanism of action of reducing severity of lung disease in Acute Respiratory Distress Syndrome (ARDS) but have failed to show consistent benefits in patient-centered outcomes. Many studies have confounding from the likely presence of ventilator-induced lung injury and steroids may have shown benefit because administration minimized ongoing inflammation incited by injurious ventilator settings. If steroids have benefit, it is likely for specific populations that fall within the heterogeneous diagnosis of ARDS. Those pediatric patients with concurrent active asthma or reactive airway disease of prematurity, in addition to ARDS, are the most common group likely to derive benefit from steroids, but are poorly studied. With the information currently available, it does not appear that the typical adult or pediatric patient with ARDS derives benefit from steroids and steroids should not be given on a routine basis.